Solubility and Thermodynamic Modeling of Sildenafil Citrate in Supercritical Carbon Dioxide - Galotto-Lopez, M; Rojas-Sepulveda, A (Elsevier B.V., 2023)
Determining the solubility of drugs in supercritical carbon dioxide (SC-CO2) is crucial to select an adequate SC-CO2 assisted technique (e.g., supercritical anti-solvent, rapid expansion of supercritical solution, etc.) to produce micro or nano sized drug particles. In this study, the solubility of sildenafil citrate (SLC) in SC-CO2 using a static method was measured and modeled for the first time. For this purpose, experiments to measure the solubility of SLC in SC-CO2 were carried out at different temperature (308 to 338 K) and pressure values (12 to 30 MPa). The solubility expressed as molar fraction and g/L of SLC in SC-CO2 was quantified in the range of 2.40 × 10−7 to 6.48 × 10−6 and 0.001 to 0.079 (g/L), respectively. Various models were used to correlate the measured solubility data, including the Soave Redlich Kwong (AARD = 14.33) and PC-SAFT theory (AARD =10.26) equations of state (EoS), the Modified Wilson s model (AARD=7.80), and Chrastil (AARD = 7.90), Bartle et al. (AARD = 8.75), Méndez-Santiago-Teja (AARD = 6.50), and Kumar-Johnston (AARD =5.30) as the density-based semi-empirical models. Finally, the approximate values of total (ΔHtotal), vaporization (ΔHvap), and solvation (ΔHsol) enthalpies were computed. © 2022 Elsevier B.V.